2008
DOI: 10.1093/icesjms/fsn179
|View full text |Cite
|
Sign up to set email alerts
|

Current reversals as determinants of intertidal recruitment on the central Oregon coast

Abstract: Dudas, S. E., Grantham, B. A., Kirincich, A. R., Menge, B. A., Lubchenco, J., and Barth, J. A. 2009. Current reversals as determinants of intertidal recruitment on the central Oregon coast. – ICES Journal of Marine Science, 66: 396–407. The influence of current reversals on intertidal invertebrate recruitment was investigated using two seasons of nearshore physical and intertidal biological observations along the central Oregon coast, an intermittent upwelling system. In 1998, upwelling periods were punctuated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 65 publications
0
43
0
Order By: Relevance
“…Although mussel recruitment was responsive to large, basin-scale, climatic fluctuations (NPGO; Menge et al 2009), identifying the exact processes that drive local-scale barnacle recruitment awaits further analysis. These processes are currently under debate, and will likely include upwelling and other more local-scale variables, including internal waves, tidal change, larval behavior, and processes leading to retention of larvae close to shore (e.g., Dudas et al 2009, Pineda et al 2009, Shanks 2009). Overall, the implication is that the dynamics of rocky intertidal communities exhibit nonlinear, speciesspecific responses to both ocean-scale and local-scale physical and biological factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although mussel recruitment was responsive to large, basin-scale, climatic fluctuations (NPGO; Menge et al 2009), identifying the exact processes that drive local-scale barnacle recruitment awaits further analysis. These processes are currently under debate, and will likely include upwelling and other more local-scale variables, including internal waves, tidal change, larval behavior, and processes leading to retention of larvae close to shore (e.g., Dudas et al 2009, Pineda et al 2009, Shanks 2009). Overall, the implication is that the dynamics of rocky intertidal communities exhibit nonlinear, speciesspecific responses to both ocean-scale and local-scale physical and biological factors.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis also means that about 60% of the variance is unexplained, and most likely is explained by smaller, regional-to local-scale factors such as coastal currents, bottom and coastal topography, larval behavior, sea breezes, fronts between water masses, tidal change, waves, and upwelling (e.g., Farrell et al 1991, Pineda 1991, Shanks and Brink 2005, Woodson et al 2007, Rilov et al 2008, Dudas et al 2009, Morgan et al 2009). Differential responses to these various smallerscale factors is the likely explanation underlying the divergent patterns of recruitment in space and time seen in mussels and barnacles along the Oregon coast (e.g., Menge et al 2009Menge et al , 2011Figs.…”
Section: Hypothesis 2: Facilitationmentioning
confidence: 98%
“…Recent works pointed out the relevance of frequency and variability of upwelling episodes in recruitment dynamics of diverse invertebrate species (Guisande et al 2001, Otero et al 2008, Pfaff et al 2011). In addition, several studies have shown lower recruitment rates in areas with persistent downwelling (Menge et al 2003) or upwelling conditions (Navarrete et al 2005, Broitman et al 2008, Dudas et al 2009b) compared to geographical areas characterized by intermittent upwelling.…”
Section: Discussionmentioning
confidence: 99%
“…In upwelling systems, mussel recruitment is associated with variability in adult abundance and fluctuations in primary productivity, upwelling intensity, and coastal currents (e.g. PORRI et al, 2006;DUDAS et al, 2009;REAUGH-FLOWER et al, 2011;but see BROITMAN et al, 2005). The wide range of variables covered in this study and the spatio-temporal resolution provided detailed information about the pelagic conditions, hence increasing the probability of finding significant relationship, even with very low recruitment.…”
Section: Relationship Among Physical Forcings Sst and Chla And The Imentioning
confidence: 99%
“…Barnacles and mussels are important components of intertidal communities and are frequently used as model organisms in recruitment studies. However, they respond differently to variations in the pelagic environment, such as changes in SST (DUDAS et al, 2009;ILES et al, 2012). Differences in larval behavior (SHANKS & BRINK, 2005) and in tolerance of recruits to environmental stress (WETHEY et al, 2011) can also explain recruitment variation between barnacles and mussels.…”
Section: Introductionmentioning
confidence: 99%